GERAKAN DAKWAH KULTURAL TGH. M. NAJMUDDIN MAKMUN DI LOMBOK - Ahyar Ahyar; L. Ahmad Zaenuri (Balai Penelitian dan Pengembangan Agama Makassar, 2020)
This paper examines the TGH. M. Najmuddin Makmun cultural da’wah in Lombok. TGH. M. Najmuddin Makmun is known as a figure of educators, leaders of the tarekat and has carried out institutional restoration of da’wah in the Sasak community. Evidenced by 300 majlis taklim and educational institutions, (TK, MTs, SMP, MA, SMA, Tahassus). This research uses descriptive qualitative with in-depth interview techniques, observation and document utilization. The findings show that the success of his da'wah was caused the power of cultural da’wah, namely through the traditional, saga or approach reveal flashbacks of the Sasak ancestral journey and examine historical sites. While his Sufitik is seen in his works such as, Tanwir Qulub, Tazkir al-Ghaafilin, Tanbih al-Muslimin, Nurussabah, Menghidupkan Hati, and story Wali Nyato’ which was taught and developed in the midst of Sasak society 40 years ago.